(Auto)Biographical Research in post-structural key: conversations with Judith Butler - Clívio Pimentel Júnior (Práxis Educativa, 2017)
In this theoretical essay, we investigated approaches and tensions between Butler‟s thoughts and the field of (Auto)Biographical Educational Research. We focused initially on historical, theoretical and methodological aspects of (Auto)Biographical Research, especially on the national scenario, highlighted in presentations of thematic dossiers, association letters and review papers. Then, we discussed the challenge involved in the approximation between the theoretical assumptions of (Auto)Biographical Research and philosophical assumptions of the Post-structural movement. Finally, we argued in defense of plausibility and theoretical consistency of approach between post-structuralism and (Auto)Biographical Research considering the possibility of invention of performative and post-metaphysical narratives of oneself.